2021
DOI: 10.1007/s10562-021-03625-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Catalytic Fixation Nitrogen Activity Under Visible Light by Molybdenum Doped Mesoporous TiO2

Abstract: An efficient photocatalyst capable of forming oxygen defects on the surface of mesoporous TiO 2 was obtained via doping molybdenum ions which can obviously broaden the absorption range of TiO 2 under visible light and reduce the recombination rate of photogenerated electron-hole pairs. The surface oxygen defects (Vo) introduced by metal molybdenum doping will adsorb and activate target molecules on the semiconductor surface. The effect of Vo content, modulated by Mo ions doping, on the photocatalytic NH 3 prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…A number of publications have presented the results of CO2 reduction using high- Additionally, previous reports concerning photocatalytic nitrogen fixation have shown that this process is mostly performed under high-power light sources. In experiments performed using modified TiO 2 and water (similar to this publication), 38.4-419.0 µmol•g −1 •h −1 of ammonia was obtained [23][24][25][26]. All of these processes were carried out using a 300 W Xe lamp.…”
Section: Sample Namementioning
confidence: 79%
“…A number of publications have presented the results of CO2 reduction using high- Additionally, previous reports concerning photocatalytic nitrogen fixation have shown that this process is mostly performed under high-power light sources. In experiments performed using modified TiO 2 and water (similar to this publication), 38.4-419.0 µmol•g −1 •h −1 of ammonia was obtained [23][24][25][26]. All of these processes were carried out using a 300 W Xe lamp.…”
Section: Sample Namementioning
confidence: 79%
“…On the other hand, Fe doping could generate oxygen vacancies and corresponding defect energy levels, and the high spin state Fe(III) prompts Fe 3d electrons to feedback to the N 1πg* orbitals to activate the adsorbed nitrogen molecules [15]. Other transition metals such as Ru, Co, Mo, and Ni have been shown to contribute to the catalytic performance when introduced as dopants into TiO 2 [16,17]. In addition to element doping, constructing heterostructures to improve the separation and transportation of photogenerated charges is also an effective means to enhance photocatalytic activity and stability.…”
Section: Metal Oxidesmentioning
confidence: 99%
“…30,31 In fact, this transition metal is one of the key components of some nitrogen-fixing enzymes in nature (i.e., Mo nitrogenase), and this has inspired researchers to use Mo as an active site for photocatalytic N 2 fixation. 32−38 However, the study of molybdenum as metal dopant in TiO 2 is very limited in the literature for the photocatalytic NRR, 38 and no example has been yet found based on colloidal NCs. To shed some light on this approach, here we explore for the first time the use of aqueous-dispersed colloidal Mo-doped TiO 2 NCs as a heterogeneous photo- catalyst for N 2 fixation to ammonia (NH 3 ) and NO x (NO 2 − , NO 3 − ) under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This approach can enhance the NRR performance by inducing changes to some surface properties of the material (e.g., formation of defects by changing the coordination environment, creation of active sites, improvement of carriers mobility and optical properties, etc. ). , Molybdenum has been selected as an inexpensive and nontoxic dopant, highly soluble in the TiO 2 anatase lattice, and potentially active to drive NRR. , In fact, this transition metal is one of the key components of some nitrogen-fixing enzymes in nature (i.e., Mo nitrogenase), and this has inspired researchers to use Mo as an active site for photocatalytic N 2 fixation. However, the study of molybdenum as metal dopant in TiO 2 is very limited in the literature for the photocatalytic NRR, and no example has been yet found based on colloidal NCs. To shed some light on this approach, here we explore for the first time the use of aqueous-dispersed colloidal Mo-doped TiO 2 NCs as a heterogeneous photocatalyst for N 2 fixation to ammonia (NH 3 ) and NO x (NO 2 – , NO 3 – ) under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%